If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2p+1)+4(2p+-3)=2p+-15
We move all terms to the left:
-3(2p+1)+4(2p+-3)-(2p+-15)=0
We add all the numbers together, and all the variables
-3(2p+1)+4(2p-3)-(2p-15)=0
We multiply parentheses
-6p+8p-(2p-15)-3-12=0
We get rid of parentheses
-6p+8p-2p+15-3-12=0
We add all the numbers together, and all the variables
=0
p=0/1
p=0
| 4(6+y)=8 | | x74-1=x-7 | | 50x=27+25 | | 3(8x1)=-21 | | 4(y-1)=3y-11 | | h/108=7/8 | | 4(y-1)=-3-11 | | 17+3(2-2)-112=7(=2)=y | | x−8π=πx | | -2x+5= -x+11 | | 0.20x+4=1.3x+2 | | 7t-16=-79 | | 6=2/3x-14 | | (2-5i)*(1435i)=0 | | -9-8=-14-8x | | 3y=2y=3 | | 1.6x=0,2 | | -17+5x=5x-25+8 | | 38=-6u+2(u+5) | | x+11)/2=-14 | | 7x-12=2x=8 | | 3x18=78 | | 18+s/5=21 | | 12x100=1200x6 | | 7x+12=8x-6 | | x/4=x-7 | | 71=5v=+11 | | 39=3-6v | | 6=8s-3/4=20 | | 3.14d=628 | | 6^x=1458 | | 2x+12+2x-8=180 |